Scuttling towards monophyly: phylogeny of the mega‐diverse genus Megaselia (Diptera: Phoridae). (2nd September 2020) - Hartop, Emily; Häggqvist, Sibylle; Ulefors, Sven Olof; Ronquist, Fredrik
Abstract: The genus Megaselia Rondani (Diptera: Phoridae) is one of the largest in the animal kingdom, with nearly 1700 described species and many remaining to be discovered. Work on this group is notoriously challenging due to the extreme species diversity, poor knowledge of higher‐level relationships and lack of molecular data. In this paper, we present the largest study to date of Megaselia relationships based on molecular data from one nuclear (28S rDNA) and three mitochondrial (ND1, COI and 16S) markers for 175 Nordic specimens representing 145 species of Megaselia, plus outgroups. Based on phylogenetic analyses of these data, we propose 22 informal Megaselia species groups, all of which match well‐supported terminal clades. Relationships among these groups, and between them and several isolated species, remain largely uncertain. Of the 22, 20 species groups fall into a moderately well‐supported monophyletic clade of 'core Megaselia '. Two species groups, the spinigera and ruficornis groups, fall outside of core Megaselia, as does the single representative of Myriophora, a genus that is included in Megaselia by some specialists. Here, we explore the morphology of these molecular species groups to aid future studies, and we discuss the implications of our findings for the generic circumscription of Megaselia . Hopefully, our results can aid further characterization of subgroups within the enormous Megaselia radiation and among its closest relatives, thus facilitating future work on this challenging but fascinating group of small flies. Abstract : Most of the species diversity of scuttle fly genus Megaselia is found within a 'core' clade. Future restriction of the genus to this lineage would render it monophyletic. Twenty‐two well‐supported species groups were found within the current circumscription of scuttle fly genus Megaselia, creating a molecular scaffold for future exploration of the radiation. A monophyletic core may have been discovered for problematic scuttle fly genus Megaselia, but many relationships may continue to be poorly resolved due to a large, rapid radiation.